1993
DOI: 10.1111/j.1432-1033.1993.tb18410.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two mutated vacuolar proteins reveals a degradation pathway in the endoplasmic reticulum or a related compartment of yeast

Abstract: The fate of a mutant form of each of the two yeast vacuolar enzymes proteinase yscA (PrA) and carboxypeptidase yscY (CPY) has been investigated. Both mutant proteins are rapidly degraded after entering the secretory pathway. Mutant PrA is deleted in 37 amino acids spanning the processing site region of the PrA pro‐peptide. The mutant enzyme shows no activity towards maturation of itself or other vacuolar hydrolases, a function of wild‐type PrA. Mutant CPY carries an Arg instead of a Gly residue in a highly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 53 publications
4
175
0
Order By: Relevance
“…It is posttranslationally translocated to the ER lumen where it is glycosylated and subsequently matured in the Golgi after which it is exported to the vacuole [7,8]. A point mutant of this protein, CPY\, have been previously demonstrated to be retained in the ER and retrotranslocated back to the cytosol, where it serves as an ERAD substrate [9,10]. Interestingly, Suzuki et al [3] have reported that in a deletion mutant of Png1 a slower rate of CPY\ degradation is observed.…”
Section: Introductionmentioning
confidence: 99%
“…It is posttranslationally translocated to the ER lumen where it is glycosylated and subsequently matured in the Golgi after which it is exported to the vacuole [7,8]. A point mutant of this protein, CPY\, have been previously demonstrated to be retained in the ER and retrotranslocated back to the cytosol, where it serves as an ERAD substrate [9,10]. Interestingly, Suzuki et al [3] have reported that in a deletion mutant of Png1 a slower rate of CPY\ degradation is observed.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, a mutated carboxypeptidase Y (CPY*) has been used as a model for misfolding of soluble luminal glycoproteins, and the process of CPY* degradation and its effects of N-glycan processing have been investigated in detail previously (Knop et al, 1996;Jakob et al, 1998). Mutant CPY carries an arginine instead of a glycine residue at position 255 of prepro-CPY (Finger et al, 1993). This mutated amino acid is located in a hydrophobic region in CPY.…”
Section: Construction and Characterization Of Misfolded Gas1mentioning
confidence: 99%
“…both CPY* (left) (28) and KWW (right) (29) was assayed in wild type, usa1⌬, USA1⌬UBL, and USA1⌬UBL-myc strains (Fig. 4C).…”
Section: Volume 285 • Number 8 • February 19 2010mentioning
confidence: 99%